Allama Iqbal And James Ward's Conception Of God: A Comparative Review - Dr.Javed Iqbal; Dr. Almas Khanum; Dr.Naila Majoka; Fahim Arshad; Dr. Muhammad Aman Ullah Khan; Mohsin Nawaz Basra; Dr. Ghazal Yaqub; Dr. Kiran Aslam; Dr. Maria Amin (Kurdish Studies, 2024)
Iqbal started to value Mc Taggart's view on the idea of personal immortality. He also noticed the resemblance between James Ward's belief in theistic pluralism and Rumi's metaphysical ideas. Shortly after, Iqbal chose Rumi as his spiritual mentor and embraced the concept of theistic pluralism. Rumi became his lifelong mentor, as he had foreseen key concepts from Nietzsche and Bergson. Iqbal realized that Rumi had a connection with James Ward on one end and with Nietzsche and Bergson on the other. Rumi is a proponent of evolution, liberation, the eternal nature of the self, and the potential for the destruction of the old to make way for the new, similar to Nietzsche. God is seen as an entirely free creative force. He is a limitless power and a force of creation. Iqbal understood that things can be derived from this force, yet the force itself cannot be derived from stationary entities. The force is the origin, while stationary entities are merely the result, becoming stagnant as they are derived from the force through limited thought and static concepts.